Deformation mechanism of an expressway embankment in warm and high ice content permafrost regions. (5th July 2017) - Yuan, Chang; Yu, Qihao; You, Yanhui; Guo, Lei
Highlights: The "thermal gathering effect" was revealed with measured data. The deformation characteristics were changed by the wider embankment. Monitoring data indicated significant increase of deformation under expressway. Deformation of expressway was determined by geothermal regime and ice distribution. Abstract: Based on monitoring data from the Qinghai-Tibet Testing Expressway (QTTE) in the Beiluhe Basin on the Qinghai-Tibet Plateau, we investigated the deformation mechanism of an expressway embankment in a typical warm and ice-rich permafrost region. Compared with the Qinghai-Tibet Highway (QTH) under similar environmental conditions, the QTTE has the following unique characteristics with respect to thermal effects and embankment deformation: (1) Under the multiplied heat of the QTTE and the thermal gathering effect, the thermal disturbance to the underlying permafrost increased by approximately 2.8 times, promoting permafrost degeneration and warming. (2) The maximum embankment settlement of the QTTE was approximately 2.5 times that of the QTH, and the maximum transverse deformation difference was 1.3 times that of the QTH. (3) The settlement of permafrost thaw and the creep of warm permafrost increased by double the rate of permafrost degradation and permafrost warming under the QTTE. (4) The wider pavement of the QTTE promoted the sunny-shady slope effect on embankment deformation. (5) The spatial distribution of ice underground contributed to the deformation difference and affected the development tendency of embankment deformation. Facing the higher construction standards of expressways, the stability of the future-built Qinghai-Tibet Expressway (QTE) would be much more serious, and more engineering failures may develop along the QTE without adequately efficient measures.